2004
DOI: 10.1369/jhc.3a6244.2004
|View full text |Cite
|
Sign up to set email alerts
|

Tyrosine Hydroxylase Induction by Basic Fibroblast Growth Factor and Cyclic AMP Analogs in Striatal Neural Stem Cells: Role of ERK1/ERK2 Mitogen-activated Protein Kinase and Protein Kinase C

Abstract: S U M M A R YNeural stem cells (NSC) with self-renewal and multilineage potential are considered good candidates for cell replacement of damaged nervous tissue. In vitro experimental conditions can differentiate these cells into specific neuronal phenotypes. In the present study, we describe the combined effect of basic fibroblast growth factor (bFGF) and dibutyryladenosine 3 Ј ,5 Ј -cyclic monophosphate (dbcAMP) on the differentiation of fetal rat striatal NSC into tyrosine hydroxylase-positive cells. Tyrosin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
19
0

Year Published

2006
2006
2020
2020

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 20 publications
(20 citation statements)
references
References 58 publications
1
19
0
Order By: Relevance
“…The expression of TH plays a crucial role in regulating the survival pathway induced by neurotrophins. Several studies have been reported that growth factors, neurotrophic factors, and bioactive peptides increases TH expression in cultured cells and tissues and supported the survival and differentiation of midbrain DA neurons (Nagatsu 1995;Theofilopoulos et al 2001;Lopez-Toledano et al 2004). In this study, we found that DRE suppressed the effects of rotenone on TH expression.…”
Section: Discussionsupporting
confidence: 67%
“…The expression of TH plays a crucial role in regulating the survival pathway induced by neurotrophins. Several studies have been reported that growth factors, neurotrophic factors, and bioactive peptides increases TH expression in cultured cells and tissues and supported the survival and differentiation of midbrain DA neurons (Nagatsu 1995;Theofilopoulos et al 2001;Lopez-Toledano et al 2004). In this study, we found that DRE suppressed the effects of rotenone on TH expression.…”
Section: Discussionsupporting
confidence: 67%
“…Neurotrophic factors are compounds that enhance the survival and differentiation of selected types of neurons and, therefore, are considered promising therapeutic agents for the treatment of neurodegenerative disorders characterized by selective degeneration of certain neuronal groups (Garcia de Yebenes and Mena 2000;Fernandez-Espejo 2004;Krieglstein 2004). In addition, they are also critical for the expansion and differentiation of neural progenitors, a new and promising tool in neuroregeneration (Palmer et al 1999;Reimers et al 2001;Bazan et al 2004;Lopez-Toledano et al 2004).…”
mentioning
confidence: 99%
“…KA increases neurite length and cell size in neurons derived from striatal EGF-NSC. Cyclic AMP may influence the growth and differentiation of neurons in culture (Nakao, 1998;Hansen et al, 2000;Lopez-Toledano et al, 2004;Kim et al, 2005). In our cultures, 1 and 100 lM KA raised intracellular cyclic AMP levels 1.6-and 1.3-fold, respectively.…”
Section: Discussionmentioning
confidence: 54%